1998
DOI: 10.1161/01.cir.97.14.1392
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Confers Resistance to Hypoxic Injury in the Adult Mammalian Cardiac Myocyte

Abstract: Taken together, the above observations demonstrate that TNF-alpha pretreatment confers resistance to hypoxic stress in the adult cardiac myocyte through a novel mechanism that appears to be different from but not necessarily exclusive of the protective response conferred by HSP 72 expression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
77
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 130 publications
(84 citation statements)
references
References 61 publications
5
77
0
2
Order By: Relevance
“…Hormonal alterations may play a pivotal role in mediating this process. Inflammatory cytokines are associated with the progression of cardiac hypertrophy,12 and low cytokine levels may be protective for myocytes, whereas persistently high levels are detrimental 13, 14. The growth hormone‐releasing peptide ghrelin has been mainly attributed to the metabolic system and changes in body composition.…”
Section: Introductionmentioning
confidence: 99%
“…Hormonal alterations may play a pivotal role in mediating this process. Inflammatory cytokines are associated with the progression of cardiac hypertrophy,12 and low cytokine levels may be protective for myocytes, whereas persistently high levels are detrimental 13, 14. The growth hormone‐releasing peptide ghrelin has been mainly attributed to the metabolic system and changes in body composition.…”
Section: Introductionmentioning
confidence: 99%
“…While low levels of cytokines may be protective for myocytes, persistently high levels are detrimental [5,6]. Interleukin (IL)-18 is chronically induced during various immune, infectious, and inflammatory conditions [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…For example, application of low concentrations of TNF␣ to isolated adult feline myocytes was shown to confer resistance to hypoxic stress (23). Similarly, when compared with wildtype mice and mice genetically deficient in either Tnfr1 or Tnfr2, mice deficient in both Tnfr1 and Tnfr2 demonstrated both a 40% increase in myocardial infarction size and increased cardiac myocyte apoptosis after ischemia was induced by coronary artery ligation (24).…”
Section: Rationale For Studying Tnf␣ Antagonists In Heart Failurementioning
confidence: 99%
“…TNF␣ production could be an epiphenomenon or could have an adaptive role in heart failure rather than being involved in the pathophysiology of the CHF. Several experimental studies have suggested that physiologic levels of TNF confer cytoprotective responses in the heart during acute ischemic injury (23,24). Moreover, low physiologic levels are likely to play an important role in tissue remodeling and repair (2).…”
Section: Ra and Atherosclerosismentioning
confidence: 99%